COMPORTAMENTO DA DOR E FLEXIBILIDADE MEDIANTE TRATAMENTO FISIOTERAPÊUTICO EM UM GRUPO DE DOR NAS COSTAS - MAURER, BRUNA D. P.; SILVA, FABRICIO R. D.; SFALCIN, JANAÍNA L.; STRASSBURGER, MARCIO J.; WINDMOLLER, POLLYANA; PILLA, SABRINA; STRASSBURGER, MONE Z. (Salão do Conhecimento, 2013)
Resumo